A Facile Approach for Tuning Optical and Surface Properties of Novel Biobased Alginate/Pote Handleable Films Via Solvent Vapor Exposure - Moreno-Serna, V (Elsevier B.V., 2021)
Novel biobased films consisting of alginate blends with poly (octanoic acid 2-thiophen-3-yl-ethyl ester) (POTE), a conducting polymer, were prepared by solution casting, and their optical, morphological, thermal, and surface properties were studied. Using UV–visible spectroscopy, atomic force microscopy (AFM), and scanning electron microscopy (SEM), the effects of tetrahydrofuran solvent vapors on the optical properties and surface morphology of biobased films with different POTE contents were studied. Results indicate that morphological rearrangements of POTE take place during the process of solvent exposure. Specifically, the solvent vapor induced the formation of POTE small crystalline domains, which allows envisioning the potential of tuning UV–visible absorbance and wettability behavior of biobased films. Finally, theoretical electronic calculations (specifically frontier molecular orbitals analysis) provided consistent evidence on POTE s preferential orientation and selectivity toward the THF-vapor medium. © 2021 Elsevier B.V.